S102 Vitamin d supplementation to prevent acute respiratory infections: systematic review and meta-analysis of individual participant data. (15th November 2016) - Martineau, AR; Jolliffe, DA; Hooper, RL; Greenberg, L; Aloia, JF; Bergman, P; Dubnov-Raz, G; Esposito, S; Ganmaa, D; Goodall, EC; Grant, C; Janssens, W; et al.
Abstract : Introduction and objectives: Randomised controlled trials of vitamin D to prevent acute respiratory infection have yielded mixed results. We conducted an individual patient data (IPD) meta-analysis to identify factors that may explain this heterogeneity. Methods: We performed an IPD meta-analysis of 25 trials of vitamin D supplementation with incidence of acute respiratory infection as a pre-specified outcome (total 11, 321 participants, aged 0 to 95 years). We used one-step logistic regression with random effects adjusting for age, sex, study duration and clustering by study. Pre-specified sub-group analyses were done to determine whether effects of vitamin D on risk of acute respiratory infection varied according to baseline 25-hydroxyvitamin D (25[OH]D) concentration or dosing regimen. Results: IPD were obtained for 10, 933/11, 321 (96.6%) participants. Vitamin D supplementation reduced risk of acute respiratory infection among all participants (adjusted Odds Ratio [aOR] 0.88, 95% CI: 0.81 to 0.96, P = 0.003; P for heterogeneity < 0.001). Sub-group analysis revealed a strong protective effect among individuals with baseline 25(OH) D < 25 nmol/L (aOR 0.62, 95% CI: 0.45 to 0.83, P = 0.002), not seen among those with higher levels (aOR 0.91, 95% CI: 0.78 to 1.05; Pinteraction = 0.01). A protective effect was also seen in individuals receiving daily or weekly vitamin D without additional bolus doses (aOR 0.81, 95% CI: 0.72 to 0.91, P < 0.001), but not in those receiving one or more bolus doses (aOR 0.97, 95% CI: 0.86 to 1.10, Pinteraction = 0.05). Vitamin D did not influence the proportion of participants experiencing at least one serious adverse event (aOR 0.98, 95% CI: 0.80 to 1.20, P = 0.83). The body of evidence contributing to these analyses was assessed as being of high quality. Conclusions: Vitamin D supplementation was safe, and it protected against acute respiratory infection overall. Very deficient individuals and those not receiving bolus doses experienced the most benefit.